Average fixation duration in infancy: Stability and predictive utility. (27th May 2022) - White, Hannah; Heck, Alison; Jubran, Rachel; Chroust, Alyson; Bhatt, Ramesh S.
Abstract: The current study examined the stability, consistency, and predictive utility of average fixation durations in infancy. In Study 1, infants' ( N = 80) average fixation duration when viewing social stimuli was found to show strong relative stability from 3.5 to 9 months of age. In Study 2, strong within‐infant consistency was found in 3.5‐month‐old infants' ( N = 73) average fixation durations to social and nonsocial stimuli. In Study 3, 3.5‐ to 9‐month‐old infants' ( N = 89) average fixation duration was found to systematically vary with parent‐reported symptoms of attention deficit hyperactivity disorder (ADHD) at 4–6 years of age. These results suggest that average fixation duration serves as a stable and systematic measure of individual differences in cognitive development beginning early in life.